(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
The article proposes an option for conducting screening studies of the degree of anthropogenic impact on the geosystems of mountainous areas. To qualitatively assess the degree of environmental destabilization under the influence of intensified economic activity, it is necessary to determine which criteria are more appropriate to choose for a particular territory. In addition, screening studies suggest that these criteria must be categorized as accessible. Based on the specifics of the study area, indicators of recreational load, water quality and the share of agricultural land were taken into account for the Central and South-Eastern Regions.